Assessment of influence of pro-health nutrition education and resulting changes of nutrition behavior of women aged 65-85 on their body content - Friedrich, Mariola; Goluch-Koniuszy, Zuzanna (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction : One of systemic changes connected to body ageing is the change of body content and the possibility of formation and/or intensification of insulin resistance, dyslipidemia and hypertension symptoms. Material and methods : The research was conducted on 68 women aged 65-85 with body mass index (BMI) of 25.3 to 44.5 kg/m 2 who have been educated for four months. The energy and nutritive value of 204 daily food rations (DFRs) was evaluated twice: first days of October and – after the diet correction and implementation of the basic rules – from the end of January. The measurements, anthropometric and body content (in 35 women under research) with the bio-impedance method was checked twice – before and after completing the education. Results : After completing the education, there was a statistically significant increase in consumption of grain products, fermented milk products, potatoes, fruit and vegetables, as well as seeds of legumes. Consumption of meat and cold meats, sugar and sweets significantly decreased. In the course of education, an individual-specific decrease in body mass of the participants was noticed, which found its reflection in positive changes of the anthropometric indicators value. A significant decrease in fat content in bodies of women under research was also noticed, which was accompanied by a slight increase in fat-free body mass and water. Conclusions : The four-month pro-health education of women influenced changes in improper nutrition habits resulting in, besides the improvement of organism functions and well-being of women under research, body mass loss and changes in content of the body.